Study on the effects of individual pitot tube inlet of a bladeless Tesla microturbine using numerical analysis - Basri, Ernnie Illyani; Basri, Adi Azriff; Salim, Farah Nur Diyana (Semarak Ilmu Publishing, 2023)
In this paper, a comprehensive numerical analysis of a bladeless Tesla microturbine is presented. Various studies on the effects of Tesla design parameters have shown promising results. However, the limitations associated with the inherent nozzle design have often highlighted the low efficiency of the turbine. Therefore, the study was carried out using computational fluid dynamics (CFD) to demonstrate the efficiency of the turbine as a function of the performance of different openings of the inlet nozzles, i.e., as 1-opening and individual pitot tube opening. In this work, a validation study was performed with the existing manuscript before further investigating the effects of the different openings of the inlet nozzles. The results show that the configuration of 4 inlets with 4 openings (4i4o) results in higher velocity and pressure distribution compared to 4 inlets with 1 opening (4i1o). Consequently, 4i4o obtained a higher torque value compared to 4i1o with a difference of 10%. Hence, the thrust and efficiency values for the 4i40 were 33.69% and 34.30%, respectively, higher compared to the 4i1o. The performance of the Tesla turbine with the specified optimal configuration increased very significantly compared to the previous research studies. It can be concluded that the introduction of the functional theory of the ‘pitot-tube’, which considers the gaps individually by having a separate inlet for each of them, had a great impact on the performance of Tesla turbine.